The Transmission of Parenting from Fathers to Sons - Hofferth, Sandra L. (2012)
OBJECTIVE: We address the extent to which parenting practices of fathers and mothers are associated with their sons’ parenting behaviors as young adults and whether adolescent behavior explains this association. DESIGN: Data come from 409 young men interviewed in the 2006 Young Adult study of the 1979 National Longitudinal Survey of Youth. RESULTS: Men whose fathers were positively involved with them when growing up report more positive parenting of their own children, a direct effect. Less harsh mothering and more positive fathering are associated with reduced adolescent behavior problems, and positive mothering is associated with positive adjustment of these young men as adolescents. However, neither adolescent problem behavior nor positive adjustment is associated with young men’s fathering of their own children, and thus does not explain the association between the fathering young men received and their own fathering behavior. CONCLUSIONS: Men’s parenting of their sons can have a long-term direct effect on how their sons parent their own children. Although parenting is associated with both positive and negative behaviors of sons during adolescence, these adolescent behaviors are not directly linked to later parenting behavior when sons have their own children. More research is needed to examine mediation mechanisms for the intergenerational transmission of parenting.